Perbandingan Respon Tanaman Terhadap Aplikasi Pupuk Majemuk: Analisis dan Temuan Utama - Mulyani, Oviyanti; Joy, Benny; Remona, Rizkiyani (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
The use of compound inorganic fertilizers in plant cultivation systems is on the rise because of their practicality, more comprehensive and homogeneous nutrient availability, and potential to reduce production costs. Different combinations of compound fertilizer products can generate a variety of responses in terms of plant growth. The aim of this investigation was to assess how plants responded to the components of their results, specifically the variations in two distinct compositions of compound fertilizers. This investigation divided 60 experimental sites into two groups, each using two distinct types of compound fertilizers. The macronutrient content of the compound fertilizers (NK and NP), distinguished them. This study employed nine treatments, which included a control (without fertilizer treatment), conventional NPK fertilizer, a combination of NPK fertilizers (3/4, and 1) doses with (1/2, 3/4, 1 and 1) doses of compound fertilizer, and a randomized block design Each treatment was repeated three times. The results of this study suggest that the application of compound fertilizer with two distinct compositions has a substantially different effect than the control treatment. In comparison to compound fertilizers with a higher potassium content, which have a yield component value of RAE 134%, the application of compound fertilizers with a higher phosphorus content can provide a higher yield component value of RAE 127.92%. The function of applying potassium-containing nutrients can produce better outcomes for corn plant than those with higher phosforus content, making it an interesting study that should be investigated further in the future